High intensity focused ultrasound (HIFU) ablation using the frequency sweeping excitation - Wang, Mingjun (2017)
High intensity focused ultrasound (HIFU) is emerging as an effective and noninvasive therapeutic modality for cancer/tumor treatment with the increasing interests and acceptance. With this technique, sufficiently high ultrasound energy is brought into a tight focus, generating the well-controlled tissue necrosis while leaving the intervening tissues unharmed. It has been used for the treatment of liver, kidney, breast, bone, prostate and pancreas cancer and uterine fibroids with great success. However, its wide adoption still faces some challenges, such as the relatively long procedure duration and unexpected tissue injury (i.e., skin burn) in the prefocal region. To overcome these issues, the efficacy and efficiency of HIFU therapy have been improved in this study by reducing the pre-focal heating as well as enlarging the lesion size. First, to better understand the propagation of HIFU burst in the biological tissue, an angular spectrum approach (ASA) with a second-order operator splitting was proposed to simulate the three-dimensional nonlinear acoustic field of a phased-array HIFU transducer in a multiple layered media with focus steering over a wide range and the generation of multiple foci. The proposed algorithm was found to have a better performance than the KZK model in the harmonics distribution along and transverse to the transducer axis in the measurement, especially the locations of pressure nodes in the focal region and grating lobes in the pre-focal region. Shifting and splitting the focus leads to the reduced acoustic pressure and lesion size, and increased pre-focal region heating. Second, the effect of electronically steering the beam of a phased array HIFU transducer on the grating lobe was evaluated. It is found that the grating lobe and main lobe increases and decreases quasi-linearly with the steering distance, respectively. But the increase of the grating lobe is much more rapid than the decrease of the main lobe. The high-frequency results in high temperature dropping in the focal region but increasing in the near field. Third, to mitigate the pre-focal heating caused by focus steering, frequency modulation method, the driving frequency continuously varying linearly during the HIFU ablation, was proposed. As a result, heat accumulated in the pre-focal region was leveraged greatly. Numerical simulation and experimental measurement using various excitations (constant frequency excitation, upward frequency sweeping, and downward frequency sweeping) showed that frequency sweeping excitations result in a temperature reduction in the pre-focal region. Additionally, it is possible to implement the HIFU ablation without cooling time using the chirp excitation. A parametric study illustrates that the long time and downward chirp is more effective in reducing the pre-focal heating. Finally, frequency sweeping excitation was further evaluated for the enhanced bubble cavitation. Both gel phantom and ex vivo studies showed that with a proper selection of the frequency sweep range and sweep time, a 50% enlargement of lesion size could be achieved. Analysis of the bubble cavitation signal captured by passive cavitation detection (PCD) in the gel phantom and porcine muscle with various approaches (i.e. STFT, filtered RMS of the cavitation signal, and the RMS between the harmonics) shows that both stable cavitation and inertial cavitation were enhanced by frequency chirp. Temperature rise correlated well with the enhanced bubble cavitation. The sweeping time and frequency sweeping range play different roles in the enhanced bubble cavitation. A short sweeping time and large frequency sweeping range are preferred in the HIFU ablation. Overall, clinical HIFU ablation using phased array design could be simulated to determine the treatment plan, and frequency sweeping during the exposure could reduce the grating lobe and enhance the bubble cavitation for larger lesion production simultaneously. These works would enhance the understanding of HIFU technology and improve its efficacy and efficiency.